Educational Policy and Teacher Professional Development: A Thematic Review - Dhungana, Siddhartha; Gnawali, Laxman (The Harvest, 2023)
Educational policy is a key factor to reinforce quality education in every nation. The policy always grows under the influence of global and local trends and needs. This article explores policy formation mechanisms and concentrates on the relationship between teacher professional developments with educational policy. It highlights major strategies of teacher professional development in the educational policy of Nepal. It uses thematic articles and research articles to discuss the policy issues from the global and local levels with issues like language policies and educational policy. It uses National Educational Policy 2076 and SSDP 2016-2023 for a detailed analysis of teacher professional development strategies projected and secured at the national level. It has used interpretive mode to discuss the teacher professional development strategies projected in national educational policy 2076.